2010
DOI: 10.1172/jci40891
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 is essential for host defense against cutaneous Staphylococcus aureus infection in mice

Abstract: Staphylococcus aureus is the most common cause of skin and soft tissue infections, and rapidly emerging antibiotic-resistant strains are creating a serious public health concern. If immune-based therapies are to be an alternative to antibiotics, greater understanding is needed of the protective immune response against S. aureus infection in the skin. Although neutrophil recruitment is required for immunity against S. aureus, a role for T cells has been suggested. Here, we used a mouse model of S. aureus cutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
596
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 574 publications
(660 citation statements)
references
References 73 publications
34
596
5
4
Order By: Relevance
“…3A). This is consistent with previous studies that have shown that IFN-gR 2/2 mice had lesion sizes and bacterial burdens similar to those of WT mice following an S. aureus skin infection (34). Overall, these results demonstrate that during acute S. aureus skin infection, IL-10 is capable of dampening down local proinflammatory responses and in particular gd + T cell responses, which facilitates persistence of the infection.…”
Section: Il-10 Contributes To Disease Pathology During Acute Sc Ssupporting
confidence: 92%
See 1 more Smart Citation
“…3A). This is consistent with previous studies that have shown that IFN-gR 2/2 mice had lesion sizes and bacterial burdens similar to those of WT mice following an S. aureus skin infection (34). Overall, these results demonstrate that during acute S. aureus skin infection, IL-10 is capable of dampening down local proinflammatory responses and in particular gd + T cell responses, which facilitates persistence of the infection.…”
Section: Il-10 Contributes To Disease Pathology During Acute Sc Ssupporting
confidence: 92%
“…11). gd + T cells have previously been shown to be critically important for controlling bacterial burden within the skin during S. aureus s.c. infection where they direct neutrophil recruitment to the skin site (34). In line with this, we observed a significant increase in gd + T cells locally in the skin at 8 h postinfection in the absence of IL-10 (Fig.…”
Section: Il-10 Contributes To Disease Pathology During Acute Sc Ssupporting
confidence: 85%
“…[37][38][39] We did not evaluate the a-toxin specific T-cell responses, which is a limitation of this study, and instead focused on evaluating the functionality of the anti-rAT antibodies generated by vaccination. Good seroresponse rates to the rAT vaccine were observed, with higher neutralizing antibody titers noted at the 50 mg rAT dose as compared to the 25 rAT mg dose in both monovalent and bivalent doses.…”
Section: Discussionmentioning
confidence: 99%
“…Both resident and circulating cd-T cells accumulate quickly around invasive pathogens and induce efficient anti-infection responses through collaboration with neighboring immune cells. 99 cd-T cells enhance the anti-infection capabilities of resident macrophages and NK cells, 100,101 promote the maturation of DCs 6,102 and improve the invasion resistance of epithelial cells. 103,104 Importantly, the dynamic interaction between cd-T cells and their neighbors induces cd-T cells in anti-infection immunity J Zheng et al 52 TCR selection of cd-T cells in situ, leading to more precise responses against specific pathogens.…”
Section: Direct Anti-infection Activity Mediated By Cd-t Cells Directmentioning
confidence: 99%
“…4,5 The roles of cd-T cells are multifaceted and correlate with their distribution and differentiation. 2 On the one hand, epidermal cd-T cells play an indispensable role in limiting and eliminating invasive pathogens and recruiting inflammatory cells to infected locations, 6,7 while skin cd-T cells promote tissue repair by producing keratinocyte growth factor. 8 On the other hand, some cd-T cells, especially IL-17-producing cd-T cells, have been confirmed to be involved in the pathogenesis of transplantation rejection, 9 autoimmune diseases, [10][11][12][13] inflammatory diseases 14,15 and allergy 16 in human and animal models.…”
Section: Introductionmentioning
confidence: 99%